Expression Pattern of the Pneumocystis jirovecii Major Surface Glycoprotein Superfamily in Patients with Pneumonia. (19th June 2020) - Schmid-Siegert, Emanuel; Richard, Sophie; Luraschi, Amanda; Mühlethaler, Konrad; Pagni, Marco; Hauser, Philippe M
Abstract: Background: The human pathogen Pneumocystis jirovecii harbors 6 families of major surface glycoproteins (MSGs) encoded by a single gene superfamily. MSGs are presumably responsible for antigenic variation and adhesion to host cells. The genomic organization suggests that a single member of family I is expressed at a given time per cell, whereas members of the other families are simultaneously expressed. Methods: We analyzed RNA sequences expressed in several clinical samples, using specific weighted profiles for sorting of reads and calling of single-nucleotide variants to estimate the diversity of the expressed genes. Results: A number of different isoforms of at least 4 MSG families were expressed simultaneously, including isoforms of family I, for which confirmation was obtained in the wet laboratory. Conclusion: These observations suggest that every single P. jirovecii population is made of individual cells with distinct surface properties. Our results enhance our understanding of the unique antigenic variation system and cell surface structure of P. jirovecii . Abstract : The 6 families of surface glycoproteins of the human pathogen Pneumocystis jirovecii were studied with RNA sequencing. A number of different isoforms of most families were expressed simultaneously, suggesting that individual cells with distinct surface of properties compose each population.